Nitrogen fixing potential of various heterotrophic Bacillus strains from a tropical estuary and adjacent coastal regions. (8th August 2017) - Yousuf, Jesmi; Thajudeen, Jabir; Rahiman, Mujeeb; Krishnankutty, Soumya; P. Alikunj, Aneesa; A. Abdulla, Mohamed H.
Abstract : In the present study, we report the nitrogen fixing potential of heterotrophic diazotrophs isolated from a tropical estuary and adjacent coastal sea. Results of the study revealed that most of the species that are capable of fixing nitrogen in the study area belongs to the genus Bacillus . The isolates from the estuary showed maximum homology with Bacillus megaterium, B. cereus, B. safencis, B. licheniformis, B. aerophilus, B. oceanisediminis, B. flexus, B. aquimaris, B. vietnamensis, and B. subterraneaus, whereas the diazotrophic isolates from coastal samples were closely related to B. subtilis, B. megaterium, B. circulans, B. aerophilus, B. flexus, and B. oceanisediminis . Experimental studies to determine the nitrogen fixation potential of isolates revealed considerable variation among different strains and the highest nitrogen fixing potential was recorded in B. megaterium (210.05 ± 7.0 nmol C2 H4 /mg protein/day) followed by B. flexus (108.76 ± 3.66 nmol C2 H4 /mg protein/day) and B. circulans (98.28 ± 4.32 nmol C2 H4 /mg protein/day). Molecular basis of nitrogen fixation by these heterotrophic Bacillus strains has been explored in terms of the presence of nifH gene in them. We observed that heterotrophic Bacillus sp. have potential ability to fix nitrogen.